The role of financial frictions during the crisis: An estimated DSGE model - Rossana Merola (National Bank of Belgium, 2013)
After the recent banking crisis in 2008, financial market conditions have turned out to be a relevant factor for economic fluctuations. This paper provides a quantitative assessment of the impact of financial frictions on the U.S. business cycle. The analysis compares the original Smets and Wouters model (2003, 2007) with an alternative version augmented with the financial accelerator mechanism à la Bernanke, Gertler and Gilchrist (1996,1999). Both versions are estimated using Bayesian techniques over a sample extended to 2012. The analysis supports the role of financial channels, namely the financial accelerator mechanism, in transmitting dysfunctions from financial markets to the real economy. The Smets and Wouters model, augmented with the financial accelerator mechanism, is suitable to capture much of the historical developments in U.S. financial markets that led to the financial crisis. The model can account for the output contraction in 2008, as well as the widening in corporate spreads and supports the argument that financial conditions have amplified the U.S. business cycle and the intensity of the recession.
Keywords: C11; E32; E44; 330; DSGE models; business cycle; financial frictions; Bayesian estimation; Konjunktur; Finanzkrise; Bayes-Statistik; Dynamisches Gleichgewicht